Do birds of a feather flock together? Factors for religious heterogamy - Fieder, Martin; Schahbasi, Alexander; Huber, Susanne (Journal of Biosocial Science, 2020)
Social cohesion - particularly with regard to the integration of migrants - is primarily measured in terms of education, labour market participation, unemployment, income levels and poverty. When seen from a historical long-term perspective (considering the migrations of Homo sapiens in the past 300,000 years) admixture merged members of diverse groups and forged - in addition to social ties - 'strong biological ties' of kinship, proposing that religious heterogamy is a long-term layer of social cohesion. Accordingly, this study investigated, on the basis of more than 600,000 men and women aged 26-35 years from Austria 2001, Germany (West) 1987, Ireland 2011, Portugal 2011, Romania 2011 and Switzerland 2000, which demographic characteristics foster religious heterogamy, controlling for various confounding factors using linear mixed modelling. By far the most important factor explaining religious heterogamy was the share of adherents to an individual's religious group in their area of residence. It can be concluded that the rate of intermarriage declines with the increasing size of an individual's religious group in their area of residence. From a long-term perspective the lack of familial ties (and conjoint offspring) between religious groups could lead to a lack of social cohesion.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Marriage; Religion; Social Cohesion